Organizational Work‐Family Culture and Working Mothers’ Affective Commitment: How Career Expectations Matter - Chang, Eunmi; Chin, Hyun; Ye, Jieun (Human Resource Management, 2014)
The research undertaken here examines how an organizational work‐family culture affects the attitudes of working mothers. This research extends the existing findings by examining two separate mediation processes: work‐family conflict and career expectations. The cases of 1,308 working mothers were analyzed using structural equation modeling. Results show that career expectations mediated the effect of an organizational work‐family culture on affective commitment while work‐family conflict did not. As an additional analysis, working mothers’ perceptions and attitudes were compared with those of 288 peers. Results disclose that working mothers were no less committed to their organization, and were even more committed than their peers early in their careers. Working mothers’ career expectations, however, were consistently lower than their peers’ expectations. Implications of these results are included. © 2014 Wiley Periodicals, Inc.